2018
DOI: 10.1159/000488460
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychiatric Diagnoses in Pediatric Chiari Malformation Type 1

Abstract: This cross-sectional study investigates the prevalence and risks for psychiatric diagnoses in a large cohort of children with Chiari malformation type 1 (CM1) presenting for neurosurgical evaluation. Children between the ages of 6 and 17 years who were evaluated and diagnosed with CM1 at a neurosurgery clinic were identified. Eighty-six participants were recruited for this study with an average age of 11 years. Parents of participants completed a pediatric medical history questionnaire and a semistructured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although these findings are suggestive and expected for CM-II, almost half of the patients had various emotional and behavioral findings. Although psychiatric evaluation of patients with CM-I has been discussed within the literature, 12 evaluation of nonmotor behaviors caused by cerebellar dysfunction in patients with CM-II is lacking. Although cerebellar pathologies are well known for coordination and movement deficits, its relationship with cognitive impairment, language disorder, executive function impairment, visuospatial deficits, regressive personality, emotional lability, and dramatic mood swings are still being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings are suggestive and expected for CM-II, almost half of the patients had various emotional and behavioral findings. Although psychiatric evaluation of patients with CM-I has been discussed within the literature, 12 evaluation of nonmotor behaviors caused by cerebellar dysfunction in patients with CM-II is lacking. Although cerebellar pathologies are well known for coordination and movement deficits, its relationship with cognitive impairment, language disorder, executive function impairment, visuospatial deficits, regressive personality, emotional lability, and dramatic mood swings are still being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the prevalence of psychiatric disorders in a sample of 86 children with a formal diagnosis of CM-I revealed elevated rates of psychiatric diagnoses, including ADHD (22.1%), anxiety (12.8%), and depression (10.5%) when compared to published norms in the general population [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to interviews with parents of 86 children with CM-1 and a review of complementary medical record data, Lacy et al reported a 10.5% prevalence of depression in pediatric CM-1 patients. 16 An analysis of the national Conquer Chiari Patient Registry database reported a 32% prevalence of depression among 768 CM-1 patients, but the data were based on patientreported symptoms and diagnostic experiences recorded through questionnaires. 17 In our surgical cohort of adult CM-1 patients, a depression prevalence of 28% was found.…”
Section: Depression Prevalence: the General Population And Cm-1 Patientsmentioning
confidence: 99%